FROM PHENOMENA AND LAWS OF NATURE TO INITIAL DATA SYMMETRY PRINCIPLES (EXPERIENCE OF RELATIONSHIP OF NATURAL SCIENCE AND THEOLOGY) - Victor Nikolaevich Pervushin (Образование и наука)
The aim of the investigation is to show a role of principles of symmetry of the initial data in formation of the consistent physical theory in a context of the newest advances in cosmology and physics of elementary particles.Methods. Methodological problems of modernity are considered on the basis of the retrospective analysis of physical theories, history of theology, comparison and generalisation of knowledge, the facts and positions from scientific, philosophical and religious spheres.Results and scientific novelty. The problems of consistency and completeness of scientific knowledge and convergence of the maintenance of religious texts and the observant scientific data in the physics and cosmology are discussed by the example of modern cosmologic models of the description of the Universe. It is proved that such convergence is claimed and actual not only concerning classification of physical processes in the Universe, including its origin from vacuum, but also in area of ontology and at forming of logics of scientific researches.Former and newest scientific achievements in the physics and cosmology are reinterpreted in a context of Hilbert geometrodynamics, added with a choice of relative standards of lengths and principles measurement of conformal symmetry.Practical significance. The author sees the further prospect of development of the scientific theory in a priority of conformal symmetry of a totality of any initial research data. So, in accordance with conformal symmetry, elementary objects of space-time are twistors that mathematically equivalent to cubits or to quantum generalisations of bits – information units. The general theory of knowledge eventually conducts to the fundamental theory of the information which, probably, will accept the name of quantum informodynamics, by analogy with quantum chromodynamics.